A study regarding unpublished letters between Charles Kiesgen and Nadia Boulanger about the Société Musicale Indépendante (SMI) - Longo Benedetti, Danieli Verônica [UNESP] (OPUS, 2020)
This article, part of a postdoctoral research study supported by CAPES, intends to reflect on the unpublished correspondence exchanged from 1926 to 1928 between Charles Kiesgen, then general secretary of the Société Musicale Indépendante (SMI) (1910-1935) and the composer Nadia Boulanger (1887-1979), then member of the steering committee of this important French musical association. During its 25 years of existence, SMI’s main activity was the realization of its concert seasons, responsible for revealing major artists of 20th century music and presenting the first performances of an impressive number of works. The 26 letters that constitute this correspondence, which is the focus of this study, are part of the private collection of the Department of Music of the Bibliothèque nationale of France (BnF) and classified “Rés. Vm. Dos 138.” In the course of these writings, it is possible to understand SMI’s mode of operation, its selection of composers, performers, the works performed during the concert seasons, and the countless difficulties faced by the association in its final years of existence, and part of SMI’s history that still remains unknown which is the object of the present investigation.
Estudo de uma correspondência inédita trocada entre Charles Kiesgen e Nadia Boulanger em torno da Société Musicale Indépendante (SMI)
Keywords: Composers; Match; Research collections; Société Musicale Indépendante-SMI; Twentieth-century music